Carbon aerogels from acetic acid catalysed resorcinol–furfural using supercritical drying for hydrogen storage - Tian, Hu-Yong; Buckley, Craig; Paskevicius, Mark; Wang, Shaobin (Elsevier BV, 2011)
Organic aerogels were derived from aceticacidcatalysedresorcinol and furfural and then dried directly in supercriticalcarbon dioxide without the use of a solvent exchange process. These aerogels were further carbonised in nitrogen and activated in CO2 in order to obtain their corresponding carbonaerogels. The carbonaerogels prepared by this method had a greater proportion of micropores in addition to a much shorter preparation time (on the order of days) than those prepared by other studies. The effect of different drying techniques on the microstructure of the wet gels was investigated by nitrogen adsorption at cryogenic liquid nitrogen temperature. Nitrogen adsorption at 77 K allowed the determination of surface areas and pore volumes, further analysed by the Dubinin–Radushkevich model and density functional theory model. The surface area and micropore volume of carbonaerogels prepared by this method increased by 19% and 12%, and accordingly, hydrogen uptake capacity was increased by 10% from 4.9 ± 0.2 wt.% to 5.4 ± 0.3 wt.% at 4.6 MPa and 77 K.